Optically controlled high temperature superconducting attenuatorand the influent duration of laser heat - LIU Lin1; YE Yu-tang1; WU Yun-feng1; LIU Juan-xiu2; CHEN Zhen-long1; WANG Yu-lin1 (Tongxin xuebao)
A new optically controlled high temperature superconducting microwave variable attenuator used in high-temperature superconducting（HTS） subsystem of satellite system was proposed.The low microwave surface resistance and excellent laser response characteristics of HTS film was used to realize the favorable properties of this attenuator.The main results conclude: Insertion loss of this attenuator is about 0.2dB,which is lower one order than conventional attenuators;Variable precision about 0.01dB can be achieved,which is lower 1~2 order than conventional attenuators.When laser power is about 45mW,the response range of HTS microstrip to laser is about 0.1dB and the duration of heat influence continue 3.5s